2014
DOI: 10.18433/j34608
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton Pump Inhibitors as Adjunct Treatment for Triple-Negative Breast Cancers. An Introductory Study

Abstract: -PURPOSE: Triple negative breast cancers (estrogen, progesterone and human epidermal growth factor 2 (HER2) receptor-negative) are among the most aggressive forms of cancers with limited treatment options. Doxorubicin is one of the agents found in many of the current cancer treatment protocols, although its use is limited by dose-dependent cardiotoxicity. This work investigates one of the ways to suppress cancer growth by inhibiting tumor cell ability to remove acid accumulated during its metabolism by proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 24 publications
1
50
1
Order By: Relevance
“…Omeprazole is a proton pump inhibitor that is capable of inhibiting acid secretion without binding H2 receptors. Other studies have shown that omeprazole can inhibit breast cancer cell proliferation in vitro and experimental metastasis in vivo , 57,58 but our results show that, unlike ranitidine, omeprazole treatment does not inhibit E0771 tumor growth.…”
Section: Discussioncontrasting
confidence: 90%
“…Omeprazole is a proton pump inhibitor that is capable of inhibiting acid secretion without binding H2 receptors. Other studies have shown that omeprazole can inhibit breast cancer cell proliferation in vitro and experimental metastasis in vivo , 57,58 but our results show that, unlike ranitidine, omeprazole treatment does not inhibit E0771 tumor growth.…”
Section: Discussioncontrasting
confidence: 90%
“…Subsequent work showed that the pH i -dependent proliferative response in cancer cells can be generated by distinct ion transport proteins, including NHE1 (Lauritzen et al, 2012), Na + -driven bicarbonate transporters (Boedtkjer et al, 2013;McIntyre et al, 2016) and the H + /K + -ATPase proton pump (Goh et al, 2014). Additionally, pH i -dependent proliferation has recently been confirmed in vivo (Grillo-Hill et al, 2015).…”
Section: Proliferation and Cell Survivalmentioning
confidence: 99%
“…Omeprazole reportedly prevented azoxymethane-induced colonic aberrant crypt foci development in male F344 rats as well as reducing HCT-116 and HCA-7 colon cancer cell growth [230]. Esomeprazole was found to inhibit MDA-MB 468 triple negative breast cancer cell growth while rabeprazole had growth inhibitory effects on MKN 28 and AGS gastric cancer cell lines [231,232]. In addition, lansoprazole has been investigated for its ability to stimulate MDA-MB-231 breast cancer cell death in a dose dependent manner [233].…”
Section: Implications For Cancer Therapy and Chemopreventionmentioning
confidence: 99%